FACTORS ASSOCIATED WITH DEATH DUE TO ROAD TRAFFIC ACCIDENT IN MUARO JAMBI REGENCY IN 2019-2021: Faktor-Faktor yang Berhubungan dengan Kematian Akibat Kecelakaan Lalu Lintas di Kabupaten Muaro Jambi pada Tahun 2019-2021 - Adiningsih, Silvia; Halim, Raden; Kalsum, Ummi (Universitas Airlangga, 2024)
Background: Traffic accidents can cause morbidity and mortality so preventive action is needed to overcome them. Purpose: to find out the factors associated with deaths from traffic accidents in Muaro Jambi Regency in 2019 to 2021. Methods: the type of research was case control. Secondary data was collected from the Muaro Jambi Resort Police Traffic Unit with a total sample 483 consist of 161 cases and 322 controls (1:2). The variables studied were the victim's age, sex, victim's role, vehicle's type, direction of collision, day of accident, time of accident, weather, road surface's type, traffic flow, availability of road markings, and shape of the road to the variables of death due to traffic accidents. To analysis the data, chi-square test and multiple logistic regression were used. Results: The risk factors for death due to traffic accidents in Muaro Jambi Regency were age, the role of victims, traffic flow, and road shape. The dominant factor was the victim's role (OR = 3.14; 95% CI = 1.87-5.44) controlled by variables of victim's age (>30 years-old OR = 1.61; 95% CI = 0.85-3.04; 18-30 years-old OR = 1.92; 95% CI = 1.01-3.68), traffic flow (OR = 1.64; 95% CI = 1.03-2.62), and road shape (OR = 1.24; 95% CI = 0.77-2.00). Conclusion: Driver aged 18-30 years, moderate to busy traffic flow, and straight roads increase the risk of death from traffic accidents. Drivers should wear traffic safety equipment such as helmets, seat-belt and increase alertness and caution when driving.